Bilateral Cryptophthalmus: First Case Report from Nepal - Pant, Nayana; Bhatta, Subash; Shrestha, Gulshan Bahadur; Thapa, Madhu (Nepalese Journal of Ophthalmology, 2021)
Introduction: Cryptophthalmus is characterized by a partial or complete casing of the eyeball by the skin. Cryptophthalmus alongside other systemic abnormalities is well-known as Fraser syndrome. It is an unusual genetic disorder with limited literature. The complexities of disease and limited experience pose challenges in its management. Case: A two-day-male neonate was brought by his parents with a complaint of swelling in the right orbital region and deformed left eye since birth. Examination revealed bilobed globular swelling in the right orbital region covered by a continuous sheet of skin from forehead to cheek with no visible ocular tissue. On the left side, there was absence of upper lid margin and eyelashes and superior symblepharon. He also had bilateral ear abnormalities and right renal agenesis. Surgical intervention was done. On the right side, removal of the globe and cyst was done. On the left side, upper eyelid reconstruction with symblepharon release was done with amniotic membrane transplantation. Conclusions: The management of cryptophthalmus is challenging. Reconstructive surgeries allow cosmesis but useful vision is rarely gained. This is the first case report from Nepal to date to the best of our knowledge.